The impact of ribbon treatment on the interconnection of solar cells withina glass free PV module. Issue 3 (18th June 2019) - Sobik, Piotr; Pawłowski, Radosław; Pluta, Anna; Jeremiasz, Olgierd; Drabczyk, Kazimierz; Kulesza-Matlak, Grażyna; Zięba, Paweł Antoni
Abstract : Purpose: The purpose of this paper is to investigate the behavior of interconnections between solar cells in a glass-free solar modules. As glass weight can be a limitation, it is still interesting to investigate other types of systems, especially when the glass was replaced with a polymeric front sheet. Such systems can be more sensitive for the solar cell interconnection ribbon fatigue. Design/methodology/approach: To examine this effect, the set of glass-based and glass-free modules were prepared using various ribbon thickness and treatment concerning its stretching or curving before lamination. Furthermore, additional reinforcement of the connection between the ribbon and the solar cell was proposed. The prepared modules were exposed to the cyclic temperature variation in the environment chamber. The number of cycles after which the interconnection maintains its conductivity was noted. Findings: Changing the outer layers into more elastic ones requires additional care for the ribbon treatment because interconnections become more sensitive for a system relative displacement. To secure interconnection before fatigue an additional curving of ribbon between solar cells can be introduced whereas the best results were obtained for a system with aluminum plate laminated as an interlayer. Originality/value: The paper presents a new system of a glass-free solar module based on epoxy-glass fiber composite as a backsheet. The glass front sheet was replaced with an elastic, transparent polymer. Such construction can be used in a system where the glass weight is a limitation. As glass has a structural function in traditional modules and limits fatigues of interconnections the proposed system requires additional ribbon treatment to preserve long module life-span.